2007
DOI: 10.1080/17477160701440455
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers are elevated in overweight Mexican-American children

Abstract: Overweight Mexican-American children had a higher concentration of inflammatory biomarkers than healthy weight children. To our knowledge, this is the first study to report that sCD14 is elevated in overweight compared with healthy weight Mexican-American children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
2
25
1
Order By: Relevance
“…TNF-a was also unrelated to the abdominal obesity of our participants and had an independent predictive value only for the decreased concentrations of HDL-C. Similar data in children were demonstrated by Steene-Johannessen et al (10) and others (26,31), while Caballero et al (11) and Aygun et al (19) reported raised TNF-a in obese children.…”
Section: Discussionsupporting
confidence: 73%
“…TNF-a was also unrelated to the abdominal obesity of our participants and had an independent predictive value only for the decreased concentrations of HDL-C. Similar data in children were demonstrated by Steene-Johannessen et al (10) and others (26,31), while Caballero et al (11) and Aygun et al (19) reported raised TNF-a in obese children.…”
Section: Discussionsupporting
confidence: 73%
“…20,37 While we are not the first group to highlight the increased disease risk associated with childhood obesity, 18,20,37,38 we are the first, to our knowledge, to demonstrate a concurrent increase in systemic inflammation and monocyte concentration in obese Mexican American children. Future research should seek to further explore the long-term relationship between the circulating markers used in the study and incidence of CVD and DM2.…”
Section: Figurementioning
confidence: 84%
“…This sample size was selected based on a previously published study from a different cohort examining other inflammatory disease biomarkers. 18 Parental consent forms were given to all students enrolled in sixth or seventh grade, and students were asked to return the forms with a parent' s signature indicating whether they wished to participate in the study. Child assent was obtained after parent consent.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,14 For example, increases in fat mass are associated with decreased production of adiponectin as well as increased production of leptin and proinflammatory cytokines (TNF-a, IL-1b, and IL-6). 15 By controlling for changes in fat mass, we are able to demonstrate that the feeding pattern described in this report mirrors body fat distributions in obese humans. Collectively, these results indicate that by increasing the amount of macronutrient fat content, it is possible to increase weight gain and reduce the number of animals needed for a desired outcome.…”
mentioning
confidence: 78%